High concentrations of waste anesthetic gases induce genetic damage and inflammation in physicians exposed for three years: A cross‐sectional study - Braz, Mariana G.; Carvalho, Lorena I. M.; Chen, Chung‐Yen O.; Blumberg, Jeffrey B.; Souza, Kátina M.; Arruda, Nayara M.; Filho, Daniel A. A.; Resende, Ludimila O.; Faria, Renata T. B. G.; Canário, Clara d'A.; Carvalho, Lídia R.; Corrêa, Camila R.; et al. (Indoor air, 2020)
This cross‐sectional study analyzed the impact of occupational waste anesthetic gases on genetic material, oxidative stress, and inflammation status in young physicians exposed to inhalational anesthetics at the end of their medical residency. Concentrations of waste anesthetic gases were measured in the operating rooms to assess anesthetic pollution. The exposed group comprised individuals occupationally exposed to inhalational anesthetics, while the control group comprised individuals without anesthetic exposure. We quantified DNA damage; genetic instability (micronucleus‐MN); protein, lipid, and DNA oxidation; antioxidant activities; and proinflammatory cytokine levels. Trace concentrations of anesthetics (isoflurane: 5.3 ± 2.5 ppm, sevoflurane: 9.7 ± 5.9 ppm, and nitrous oxide: 180 ± 150 ppm) were above international recommended thresholds. Basal DNA damage and IL‐17A were significantly higher in the exposed group [27 ± 20 a.u. and 20.7(19.1;31.8) pg/mL, respectively] compared to the control group [17 ± 11 a.u. and 19.0(18.9;19.5) pg/mL, respectively], and MN frequency was slightly increased in the exposed physicians (2.3‐fold). No significant difference was observed regarding oxidative stress biomarkers. The findings highlight the genetic and inflammatory risks in young physicians exposed to inhalational agents in operating rooms lacking adequate scavenging systems. This potential health hazard can accompany these subjects throughout their professional lives and reinforces the need to reduce ambient air pollution and consequently, occupational exposure.